Comparative Analysis Revealed Intrageneric and Intraspecific Genomic Variation in Chloroplast Genomes of Actinidia spp. (Actinidiaceae, Viridiplantae) - Maria Gladysheva-Azgari; Fedor Sharko; Natalia Slobodova; Kristina Petrova; Eugenia Boulygina; Svetlana Tsygankova; Irina Mitrofanova (Horticulturae, 2023)
About ten species of the genus Actinidia Lindl. are known as cultivated plants—alongside the most known A. chinensis var. deliciosa, there are many others, including Far-Eastern cold-hardy kiwifruits such as A. arguta, A. kolomikta, and A. polygama. Unlike most plant species, in which the chloroplast genome is maternally inherited, the family Actinidiaceae possesses a complex system of plastid inheritance with possible transmission through both maternal and paternal lines. The main aim of this work was the assembly of the plastid genomes of three species of Actinidia, their comparison with already-available sequences from databases, and evolutionary analyses. We discovered that the gene composition and gene sequences are conserved; the studied species are either subject to purifying selection or not subject to selection at all (with some exceptions, such as the ycf2 gene). However, the chloroplast chromosomes of some Actinidia species have undergone significant structural rearrangements, leading to the persistence of two main forms, both on an intrageneric and intraspecific level. These results expand our understanding of plastid genomics and genetic diversity within the genus Actinidia, providing a basis for future research in molecular marker development, phylogenetic analysis, and population studies.